Structural, elastic, and, strain induced electronic and magnetic properties of half-Heusler alloys MnSnX (X = Ni, Cu, and Pd) - Chaudhary, Uchit; Dahal, Subash; Guragain, Bhupal; Kaphle, Gopi Chandra; Yadav, Shashit Kumar (BIBECHANA, 2026)
Half-metallic (HM) ferromagnetic materials have garnered significant attention due to their potential applications in solid-state electronic devices. Strain manipulation offers a promising avenue for tuning the physical properties of such materials. In this regard, the structural, elas- tic, and strain effect on electronic and magnetic properties of half-HeuslerMnSnX (X = Ni, Cu, and Pd) alloys have been studied in this work. Our findings revealed that these compounds exhibit negative formation and cohesive energies, indicative of their chemical stability and po- tential for experimental synthesis, with the exception of MnSnCu. Elastic property analysis further demonstrated the mechanical stability of all compounds, yet their inherent brittleness. We observed HM behaviour under uniform compressive strain ranging from -5% to -14% in MnSnNi and MnSnPd, with band gaps between 0.499 and 0.822 eV calculated using the GGA method whereas MnSnCu does not exhibit HM character. This is a noteworthy departure from the unstrained system (0%). The mBJ method further validated HM characteristics, except for MnSnCu under compressive strain thresholds of ≤ −6% and ≤ −12% for MnSnNi and MnSnPd, respectively. The magnetic properties under uniform compressive strains, where HM nature is achieved, conform to the Slater-Pauling 18-electron rule, boasting 100% spin polarization near the Fermi level. This polarization primarily stems from the transition metal Mn, with minor contributions from Ni, Pd, and Sn. In light of our findings, we propose that the electronic and magnetic attributes of these materials can be enhanced through the application of strains, potentially making them attractive for spintronic applications.